1966
DOI: 10.1126/science.154.3750.772
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Alpha-Toxin: Effects on Artificial Lipid Spherules

Abstract: Staphylococcal alpha-toxin induces the release of previously sequestered anions or glucose from artificial phospholipid spherules, an effect abolished by specific antitoxin. Alphatoxin resembles streptolysin S in releasing anions or glucose from spherules prepared without cholesterol, and can be distinguished from the membrane-active polyene amphotericin B, which preferentially disrupts spherules containing cholesterol. It may affect biological structures by a similiar interaction with membrane phospholipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 13 publications
(1 reference statement)
2
22
0
Order By: Relevance
“…Previous studies (Weissmann, Sessa & Bernheimer, 1966 ;Freer, Arbuthnott & Bernheimer, 1968) on the activity of this cytolytic toxin against artificial lipid membranes (liposomes), consisting of lecithin, cholesterol and charged fatty acid derivatives, showed the following : (i) disruption of the lamellar structure and release of sequestered marker molecules; (ii) appearance on membrane surfaces of ring structures morphologically identical with a,,,; and (iii) disappearance of toxic activity. Similar effects have been observed following the interaction of staphylococcal a-toxin with mammalian erythrocytes (Freer et al I 968).…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies (Weissmann, Sessa & Bernheimer, 1966 ;Freer, Arbuthnott & Bernheimer, 1968) on the activity of this cytolytic toxin against artificial lipid membranes (liposomes), consisting of lecithin, cholesterol and charged fatty acid derivatives, showed the following : (i) disruption of the lamellar structure and release of sequestered marker molecules; (ii) appearance on membrane surfaces of ring structures morphologically identical with a,,,; and (iii) disappearance of toxic activity. Similar effects have been observed following the interaction of staphylococcal a-toxin with mammalian erythrocytes (Freer et al I 968).…”
Section: Introductionmentioning
confidence: 90%
“…demonstrated that streptolysin-S, a streptococcal hemolytic exotoxin, modulated cation permeability of multilamellar 150 nm liposomes [94]. The concept was further examined in a subsequent study in which staphylococcal α-toxin was found to increase ion permeability of liposomes [95]. Following these early studies, liposomes were frequently used to examine the mechanisms and properties of different membrane-active toxins.…”
Section: Cell-membrane Mimicking Nanoparticles For Toxin Neutralizmentioning
confidence: 99%
“…Such examples include the membrane attack complex of complement (163), the mellitin component of bee venom (245), and bacterial toxins (239) . He also mentions instances in which proteins may have been assembled asymmetrically into phospholipid bilayers of vesicles formed during membrane reconstitution experiments.…”
Section: Posttranslational Transfer Of Polypeptides To Their Sites Ofmentioning
confidence: 99%